Uso de álcool entre adolescentes em vulnerabilidade social: subsídios para programas preventivos. - Santos, Elaine Lucas dos [UNIFESP] (2018)
The use of alcohol in adolescence is a problem that stands out as a priority in public health, leading to the creation of preventive initiatives around the world. There is a lack of interventions based on scientific evidence developed for the Brazilian context. In order to develop future preventive interventions for adolescents in social vulnerability, the objective of this study was to investigate the perspectives of adolescents, mothers, educators and experts in substances studies about their beliefs and expectations related to adolescents' use of alcohol. Methods: This is a qualitative study that used focus group technique and individual interviews. Participated a total of 153 adolescents and 33 educators from Youth Centers and Public Schools of the São Paulo city, 8 mothers and 8 specialists in substance use. Data were recorded, transcribed, submitted to the analysis of contents and reports were based on COREQ guidelines (COnsolidated criteria for REporting Qualitative research). Results and discussion: Adolescents reported several risk behaviors, alcohol use, with emphasis on issues related to gender and violence, which are enhanced by contextual factors involving the Pancadões, the main scenarios of alcohol use by adolescents in the outskirts of São Paulo. With regard to the ways of dealing with the issues related to the use of alcoholic beverages in adolescence, differences in prevention-related expectations were observed. Among parents and educators, expectations of frightening and controlling the behavior of adolescents predominate, they refer to the expectation of critical disclosure and responsible autonomy. The adolescents' perception has been more aligned with specialists’ view and the scientific literature. Final considerations: The results demonstrate divergences of expectations that may represent obstacles to our processes to prevent risks related to alcohol consumption. These data highlight the need for the development of interventions that contemplate and reduce differences in the conceptions of adolescents and, parents and educators.